Clmp Regulates AMPA and Kainate Receptor Responses in the Neonatal Hippocampal CA3 and Kainate Seizure Susceptibility in Mice - Jang, Seil; Yang, Esther; Kim, Doyoun; Kim, Hyun; Kim, Eunjoon (Frontiers in Synaptic Neuroscience, 2020)
Synaptic adhesion molecules regulate synapse development through trans-synaptic adhesion and assembly of diverse synaptic proteins. Many synaptic adhesion molecules positively regulate synapse development; some, however, exert negative regulation, although such cases are relatively rare. In addition, synaptic adhesion molecules regulate the amplitude of postsynaptic receptor responses, but whether adhesion molecules can regulate the kinetic properties of postsynaptic receptors remains unclear. Here we report that Clmp, a homophilic adhesion molecule of the Ig domain superfamily that is abundantly expressed in the brain, reaches peak expression at a neonatal stage (week 1) and associates with subunits of AMPA receptors (AMPARs) and kainate receptors (KARs). Clmp deletion in mice increased the frequency and amplitude of AMPAR-mediated miniature excitatory postsynaptic currents (mEPSCs) and the frequency, amplitude, and decay time constant of KAR-mediated mEPSCs in hippocampal CA3 neurons. Clmp deletion had minimal impacts on evoked excitatory synaptic currents at mossy fiber-CA3 synapses but increased extrasynaptic KAR, but not AMPAR, currents, suggesting that Clmp distinctly inhibits AMPAR and KAR responses. Behaviorally, Clmp deletion enhanced novel object recognition and susceptibility to kainate-induced seizures, without affecting contextual or auditory cued fear conditioning or pattern completion-based contextual fear conditioning. These results suggest that Clmp negatively regulates hippocampal excitatory synapse development and AMPAR and KAR responses in the neonatal hippocampal CA3 as well as object recognition and kainate seizure susceptibility in mice.